EFFECT OF LEVELS OF ANIMAL DIETARY PROTEIN AND PROBIOTIC ADDITIVES (SACCHAROMYCES CEREVISIAE AND BACILLUS SUBTILIS) ON INSULIN, TSH AND GROWTH HORMON OF AWASSI SHEEP - A. F. Al-Abedi; A. A. Saeed; K. S. Al-Huosyney (Al-Qadisiyah Journal For Agriculture Sciences, 2020)
To maintain the body on its metabolic activities, including catabolic and anabolic processes, it needs tools. Insulin, thyroxine, growth hormone and other hormones are considered the tools that contribute to regulate metabolism in living organism. The studies that interest in that scope and applied on ruminants are too scarce, therefore the current research has studied the effect of levels of dietary protein and probiotic additives (Live Saccharomyces cerevisiae more than 3.0×1013 CFU and  bacillus subtilis more than 4.0 ×109CFU) on insulin, TSH and growth hormone of Awassi sheep. In this study was used sixteen sheep, animals have divided to four groups (four animals in each group). The first group fed with crude protein(cp) (12%) with no probiotics, the second group fed with cp (12%) plus 1 kg/ton probiotic, the third group fed with cp (14%) with no probiotics, and finally the fourth one fed with cp (14%) plus 1 kg/ton probiotic. The main results have shown that there is significant increase (P<0.01) in the insulin concentration between class cp (12%) comparing with class cp (14%). Regarding the interaction treatments, there is a significant increase (P<0.05) between cp (12%) plus no probiotic comparing with cp (14%) plus no probiotic and with cp (14%) plus probiotic, and between cp (12%) plus probiotic comparing with cp (14%) plus probiotic. Concerning TSH, the results shows that there is a significant increase (P<0.01) between cp (12%) plus no probiotic comparing with cp (12%) plus probiotic and with cp (14%) plus no probiotic, and between cp (14%) plus probiotic comparing with cp (12%) plus probiotic and with cp (14%) plus no probiotic. Regarding growth hormone, results haven’t shown any significant differences among any classes whether in main effects or in interaction treatments. We could conclude that, there are significant effects of dietary protein levels plus probiotic additives on insulin and TSH concentrations but not on growth hormone concentration.